Spatial working memory in a disappearing object task is impaired in female but not male dogs with chronic osteoarthritis - Melissa Smith; Joanna C. Murrell; Michael Mendl (Animal Cognition)
Abstract Chronic pain in humans is associated with impaired working memory but it is not known whether this is the case in long-lived companion animals, such as dogs, who are especially vulnerable to developing age-related chronic pain conditions. Pain-related impairment of cognitive function could have detrimental effects on an animal’s ability to engage with its owners and environment or to respond to training or novel situations, which may in turn affect its quality of life. This study compared the performance of 20 dogs with chronic pain from osteoarthritis and 21 healthy control dogs in a disappearing object task of spatial working memory. Female neutered osteoarthritic dogs, but not male neutered osteoarthritic dogs, were found to have lower predicted probabilities of successfully performing the task compared to control dogs of the same sex. In addition, as memory retention interval in the task increased, osteoarthritic dogs showed a steeper decline in working memory performance than control dogs. This suggests that the effects of osteoarthritis, and potentially other pain-related conditions, on cognitive function are more clearly revealed in tasks that present a greater cognitive load. Our finding that chronic pain from osteoarthritis may be associated with impaired working memory in dogs parallels results from studies of human chronic pain disorders. That female dogs may be particularly prone to these effects warrants further investigation.